Peningkatan Hasil Belajar IPA pada Materi Alat Indra dengan Pendekatan Saintifik - Molli Wahyuni; Masrul Masrul; Merya Melly Sesa (Departement of Mathematics Education, 2022)
This study aims to improve science learning outcomes in sensory material with a scientific approach in class IV SD Pahlawan. The formulation of the problem in this study is how are the results of learning science on sensory material after using a scientific approach in class IV SD Pahlawan. This research was conducted in class IV SD Pahlawan. This research was carried out in two cycles, and the time of the research was carried out from November to December 2021. The objects of this research were 25 grade IV students, with 12 male students and 13 female students. Data collection techniques used in this study are test, observation, and documentation techniques. Based on the results of the study, it can be concluded that student learning outcomes on sensory instruments in class IV SD Pahlawan in cycle I are still quite adequate with an average of 72.40. Furthermore, out of 25 students, only 16 students or 64% achieved completeness individually. Student learning outcomes in cycle II were quite good with an average of 80.80, and 25 students, 23 students or 92% achieved completeness individually. Thus it can be concluded that the scientific approach can improve science learning outcomes in sensory material in class IV SD Pahlawan.